Development of a culturally responsive special needs education framework for Alangan-Mangyan learners with disabilities - Salva, Royce A.
Rooted in the intersectionality framework, this phenomenological exploration unveils the lived experiences of learners with disabilities from the Alangan-Mangyan communities in Naujan, Oriental Mindoro. Their descriptions of their intersecting identities and the educational issues they face were examined as a basis for developing a culturally responsive special needs education (CRSNE) framework. In total, nine research participants from three indigenous communities met the inclusion criteria. Correspondingly, key informants from the Alangan-Mangyan communities, government organizations, and national and local education agencies, among others, were identified. The datasets of the participants and the key informants were analyzed using the seven-step modified van Kaan method of Moustakas and the six-step thematic analysis of Braun and Clarke, respectively. The data analysis resulted in the emergence of six overarching themes. The first two themes zero in on the participants’ descriptions of their intersecting indigeneity and disability, which highlight their indigenous perspectives and practices in relation to disability (i.e., perceived definitions, causes, manifestations, and management approaches). Meanwhile, the succeeding themes disclosed their issues in equity and accessibility, social, psychological, emotional, and motivational, and cultural aspects. These themes reveal the five fundamental qualities of the participants’ universal essence—generosity, relationships, adversities, convergence, and expression of self-determination (GRACE). Thereafter, the study concludes with a proposed five-stage CRSNE framework. Described as both perceptive and reflective, the framework intends to alleviate the systematic barriers that prevent indigenous learners with disabilities from participating fully in the educational process.